3/4 X x = 5/7 x : 3/5 = 11 5/7 : x = 1/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,Cách 1: (6/11 + 5/11 ) x 3/7 Cách 2 :(6/11 + 5/11) x 3/7
= 1 x 3/7 =6/11 x 3/7 + 5/11 x 3/7
= 3/7 = 18/77 + 15/77
= 3/7
b, Cách 1:3/5 x 7/9 - 3/5 x 2/9 Cách 2 :3/5 x 7/9 - 3/5 x 2/9
= 7/15 - 2/15 = 3/5 x (7/9 - 2/9 )
= 1/3 = 3/5 x 5/9
= 1/3
c, Cách 1:(6/7 - 4/7) : 2/5 Cách 2: ( 6/7- 4/7 ) : 2/5
= 2/7 : 2/5 = 6/7 : 2/5 - 4/7 : 2/5
= 5/7 = 15/7 - 10/7
= 5/7
d,Cách 1:8/15 : 2/11 + 7/15 : 2/11 Cách 2:8/15 : 2/11 +7/15 : 2/11
= 88/30 + 77/30 =(8/15+7/15) :2/11
= 11/2 = 1 : 2/11
= 11/2
Bài 2 cậu tự làm nhé !
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{1}{5}+\dfrac{4}{11}+\dfrac{1}{5}+\dfrac{7}{11}=\dfrac{1}{5}+\left(\dfrac{4}{11}+\dfrac{7}{11}\right)=\dfrac{1}{5}+1=\dfrac{1}{5}+\dfrac{5}{5}=\dfrac{6}{5}\)
b) \(\dfrac{3}{5}\times\dfrac{4}{7}+\dfrac{2}{5}\times\dfrac{4}{7}=\left(\dfrac{3}{5}+\dfrac{2}{5}\right)\times\dfrac{4}{7}=1\times\dfrac{4}{7}=\dfrac{4}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2: \(=\dfrac{-2}{75}+\dfrac{5}{39}=\dfrac{33}{325}\)
3: \(=\dfrac{6}{11}\left(\dfrac{4}{9}+\dfrac{5}{9}\right)=\dfrac{6}{11}\)
4: \(=\dfrac{7}{19}\left(\dfrac{5}{13}+\dfrac{8}{13}-1\right)=-2\cdot\dfrac{7}{19}=-\dfrac{14}{19}\)
5: \(=\dfrac{2}{7}\left(\dfrac{4}{23}-\dfrac{27}{23}+1\right)=0\)
6: \(=\dfrac{3}{8}\left(\dfrac{3}{7}+\dfrac{4}{7}\right)+\dfrac{11}{8}=\dfrac{3}{8}+\dfrac{11}{8}=\dfrac{14}{8}=\dfrac{7}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =>x-2/5=3/4:1/3=3/4*3=9/4
=>x=9/4+2/5=45/20+8/20=53/20
b: =>x-2/3=7/3:4/5=7/3*5/4=35/12
=>x=35/12+2/3=43/12
c: 1/3(x-2/5)=4/5
=>x-2/5=4/5*3=12/5
=>x=12/5+2/5=14/5
d: =>2/3x-1/3-1/4x+1/10=7/3
=>5/12x-7/30=7/3
=>5/12x=7/3+7/30=77/30
=>x=77/30:5/12=154/25
e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)
=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)
=>x=19/7:23/28=76/23
f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5
=>13/12x=1/5+3/2+4/3+5/4=257/60
=>x=257/65
i: =>x^2-2/5x-x^2-2x+11/4=4/3
=>-12/5x=4/3-11/4=-17/12
=>x=17/12:12/5=85/144
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(=\dfrac{3}{3}+\dfrac{4}{3}=\dfrac{7}{3}\)
b)\(=\dfrac{5}{9}\times\dfrac{3}{2}=\dfrac{15}{18}=\dfrac{5}{6}\)
d)\(=\left(\dfrac{12}{8}-\dfrac{3}{8}\right)\times2=\dfrac{9}{8}\times2=\dfrac{18}{8}=\dfrac{9}{4}\)
c)\(=\dfrac{4}{3}-\dfrac{5}{6}=\dfrac{8}{6}-\dfrac{5}{6}=\dfrac{3}{6}=\dfrac{1}{2}\)
a) 1 + 4/3 = 7/3
b) 5/9 : 2/3 = 5/6
c ) 4/3 -1/3 x 5/2
= 1 x 5/2
= 5/2
d) ( 3/2 - 3/8) : 1/2
= 9/8 : 1/2
= 9/4
e) 15/16 : 3/8 x 3/4
= 5/2 x 3/4
= 15/8
f) 7/19 x 1/3 x 7/19 x 2/3
= 7/19 x (1/3 x 2/3)
= 7/19 x 2/9
= 14/171
g) 3/5 x 8/27 x 25/3
= 3/5 x 25/3 x 8/27
= 5 x 8/27
= 40/27
h) 1/5 + 4/11 + 4/5 + 7/11
= (1/5 + 4/5) + (4/11 + 7/11)
= 1 + 1
= 2
a) X + 1/4 = 5/8
b) X - 3/5 = 1/10
c) X x 2/7 = 6/11
d) X : 3/2 = 1/4
đ) 7/4 - X = 5/7
e) 5/4 : x = 1/8
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,x+\dfrac{1}{4}=\dfrac{5}{8}\)
\(\Leftrightarrow x=\dfrac{5}{8}-\dfrac{1}{4}\)
\(\Leftrightarrow x=\dfrac{5}{8}-\dfrac{2}{8}\)
\(\Leftrightarrow x=\dfrac{3}{8}\)
\(b,x-\dfrac{3}{5}=\dfrac{1}{10}\)
\(\Leftrightarrow x=\dfrac{1}{10}+\dfrac{3}{5}\)
\(\Leftrightarrow x=\dfrac{1}{10}+\dfrac{6}{10}\)
\(\Leftrightarrow x=\dfrac{7}{10}\)
\(c,x\times\dfrac{2}{7}=\dfrac{6}{11}\)
\(\Leftrightarrow x=\dfrac{6}{11}:\dfrac{2}{7}\)
\(\Leftrightarrow x=\dfrac{6}{11}\times\dfrac{7}{2}\)
\(\Leftrightarrow x=\dfrac{42}{22}\)
\(\Leftrightarrow x=\dfrac{21}{11}\)
\(d,x:\dfrac{3}{2}=\dfrac{1}{4}\)
\(\Leftrightarrow x=\dfrac{1}{4}\times\dfrac{3}{2}\)
\(\Leftrightarrow x=\dfrac{3}{8}\)
\(đ,\dfrac{7}{4}-x=\dfrac{5}{7}\)
\(\Leftrightarrow x=\dfrac{7}{4}-\dfrac{5}{7}\)
\(\Leftrightarrow x=\dfrac{49}{28}-\dfrac{20}{28}\)
\(\Leftrightarrow x=\dfrac{29}{28}\)
\(e,\dfrac{5}{4}:x=\dfrac{1}{8}\)
\(x=\dfrac{5}{4}:\dfrac{1}{8}\)
\(\Leftrightarrow x=\dfrac{5}{4}\times8\)
\(\Leftrightarrow x=\dfrac{40}{4}\)
\(\Leftrightarrow x=10\)
3/4 X x = 5/7
\(x=\dfrac{5}{7}:\dfrac{3}{4}\)
\(x=\dfrac{5}{7}\times\dfrac{4}{3}\)
\(x=\dfrac{20}{21}\)
x : 3/5 = 11
\(x=11\times\dfrac{3}{5}\)
\(x=\dfrac{33}{5}\)
5/7 : x = 1/4
\(x=\dfrac{5}{7}:\dfrac{1}{4}\)
\(x=\dfrac{5}{7}\times4\)
\(x=\dfrac{20}{7}\)
`3/4 xx x=5/7`
`x=5/7:3/4`
`x=5/7xx4/3=20/21`
_____________________________
`x:3/5=11`
`x=11xx3/5=33/5`
_______________________________
`5/7:x=1/4`
`x=5/7:1/4`
`x=5/7xx4=20/7`